Routine interim disease assessment in patients undergoing induction chemotherapy for acute myeloid leukemia: Can we do better?. Issue 3 (11th January 2016) - Campuzano‐Zuluaga, Germán; Deutsch, Yehuda; Salzberg, Matthew; Gomez, Alexandra; Vargas, Fernando; Elias, Roy; Kwon, Deukwoo; Goodman, Mark; Ikpatt, Offiong F.; Chapman, Jennifer R.; Watts, Justin; Vega, Francisco; et al.
Abstract : The presence of >5% blasts at "day 14" (D14), in patients undergoing induction chemotherapy for acute myeloid leukemia (AML) is problematic. It is unclear if a second course of chemotherapy for early persistent disease will alter outcome in these patients. We conducted a retrospective study of AML patients undergoing induction chemotherapy where diagnostic, interim (around day 14), and recovery (days 21–42) bone marrow (BM) evaluations were available for review. Of the 113 patients included in the final analysis, 99 (87.6%) achieved CR at hematologic recovery. At D14, 90 patients (79.6%) had <5% blasts and of these, 87 (96.7%) ultimately achieved CR. At D14, Twenty‐three (20.4%) patients had residual leukemia (>5% blasts). Of these, 11 (47.8%) received a second course of chemotherapy (double induction [DI]) and 12 (52.2%) were observed until count recovery (single induction [SI]). No significant difference in CR rates was observed between these two groups (58.3% DI group vs. 45.5% SI group, P value = 0.684). In our analysis, D14 BM evaluation did not uniformly identify patients with primary induction failure. To unequivocally determine the value of a D14 marrow assessment in AML, prospective studies in the context of large cooperative group trials are required. Considering our findings and similar reports from others, we propose that D14 marrow assessment should be individualized, and that other factors, such as cytogenetics and early peripheral blood blast clearance should be considered, to identify patients most likely to benefit from interim disease assessment during AML induction therapy. Am. J. Hematol. 91:277–282, 2016. © 2015 Wiley Periodicals, Inc.